Fabrication of Tetra-Substituted Copper(II) Phthalocyanine-Graphene Modified Pencil Graphite Electrode for Amperometric Detection of Hydrogen Peroxide - Gorduk, Ozge; Gorduk, Semih; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2020)
In this study, tetra-substituted copper(II) phthalocyanine-graphene modified pencil graphite electrode (CuPc-Gr/PGE) was developed for the amperometric determination of hydrogen peroxide (H2O2) for the first time in the literature. The developed non-enzymatic electrode platform was electrochemically characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) methods. Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) methods were also used for surface characterization of the modified electrode. The response to H(2)O(2)at the working potential of -0.4 V is linear in the 0.1 mu M to 100 mu M concentration range in PBS pH 7.0. The limit of detection (LOD) and limit of quantitation (LOQ) are 0.045 and 0.15 mu M, respectively. Good selectivity was observed within physiological interference species such as ascorbic acid, dopamine, uric acid, and glucose. Additionally, amount of H(2)O(2)was determined using the novel produced non-enzymatic sensor with satisfactory results in beverage samples. These consequences imply that the CuPc-Gr/PGE displays effective electrocatalytic activity for the reduction of H2O2, indicating it has capability use for the detection of H2O2.
Keywords: Graphene; Phthalocyanine; Hydrogen peroxide (H2O2); Amperometry; Voltammetry; ELECTROCHEMICAL DETERMINATION; ELECTROCATALYTIC ACTIVITY; CARBON NANOTUBES; QUANTUM DOTS; SENSOR; NANOPARTICLES; H2O2; GLUCOSE; GOLD; PAPER; Materials Science; Physics